Nonequilibrium landscapes and nature conservation in the Białowieża Forest - Kowalewska, Agata (Polskie Studia Krajobrazowe, 2019)
Traditional conceptualizations presume that landscape and nature in general are characterized by a striving for balance. In consequence, environmental protection chiefly consists in conservation of the existing state, without making allowances for the dynamic changes caused by vital processes taking place in those landscapes, human and non-human alike. The current dispute concerning the protection of the Białowieża Forest is nothing but an upshot of the differences between the involved with respect to what should be protected on top of how it should be done. This study outlines the problems deriving from conceptualizations of nature and landscape as static entities and comes forward with a proposal of conceiving landscape not as an “image of the land”1 but a corporeal experience of being in a space, on which climate change, civilizational and social transformation, political decisions, and bark beetles all have their impact.